Soft Actuators Materials, Modeling, Applications, and Future Perspectives - Asaka, Kinji; Okuzaki, Hidenori; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is the second edition of Soft Actuators, originally published in 2014, with 12 chapters added to the first edition. The subject of this new edition is current comprehensive research and development of soft actuators, covering interdisciplinary study of materials science, mechanics, electronics, robotics, and bioscience. The book includes contemporary research of actuators based on biomaterials for their potential in future artificial muscle technology. Readers will find detailed and useful information about materials, methods of synthesis, fabrication, and measurements to study soft actuators. Additionally, the topics of materials, modeling, and applications not only promote the further research and development of soft actuators, but bring benefits for utilization and industrialization. This volume makes generous use of color figures, diagrams, and photographs that provide easy-to-understand descriptions of the mechanisms, apparatus, and motions of softactuators. Also, in this second edition the chapters on modeling, materials design, and device design have been given a wider scope and made easier to comprehend, which will be helpful in practical applications of soft actuators. Readers of this work can acquire the newest technology and information about basic science and practical applications of flexible, lightweight, and noiseless soft actuators, which differ from conventional mechanical engines and electric motors. This new edition of Soft Actuators will inspire readers with fresh ideas and encourage their research and development, thus opening up a new field of applications for the utilization and industrialization of soft actuators. .
Progress and Current Status of Materials and Properties of Soft Actuators -- Current Status of Applications and Markets of Soft Actuators -- Electromagnetic Heating -- Thermo-Responsive Nanofiber Mats Fabricated by Electrospinning -- Evolution of Self-Oscillating Polymer Gels as Autonomous Soft Actuators -- Polyrotaxane Actuators -- Ionic Conductive Polymers -- Conducting Polymers -- Humidity-Sensitive Conducting Polymer Actuators -- Carbon Nanotube/Ionic Liquid Composites -- Ion Gels for Ionic Polymer Actuators -- Ionic Liquid/Polyurethane/PEDOT:PSS Composite Actuators -- Dielectric Gels -- Dielectric Elastomers -- Piezoelectric Polymers -- Thermal and Electrical Actuation of Liquid Crystal Elastomers/Gels -- Spiropyran-Functionalized Hydrogels -- Photomechanical Energy Conversion with Cross-Linked Liquid-Crystalline Polymers -- Photoredox Reaction -- Magnetic Fluid Composite Gels -- Magnetic Particle Composite Gels -- Molecular Mechanism of Electrically Induced Volume Change of Porous Electrodes -- Computational Modeling of Mechanical Sensors Using Ionic Electro-Active Polymers -- Distributed Parameter System Modeling -- Control of Electro-Active Polymer Actuators with Considering Characteristics Changes -- Motion Design-A Gel Robot Approach -- Motion Control -- IPMC Actuation Mechanisms and Multi-Physical Modeling -- Sensing Properties and Physical Model of Ionic Polymer -- Modelling of Dielectric Elastomer Actuator -- Modelling of Dielectric Gel using Multi-Physics Coupling Theory -- Modeling and Control of Fishing-Line/Sewing-Thread Artificial Muscles (Twisted and Coiled Polymer Fibers, TCPFs) -- Underwater Soft Robots -- IPMC Actuator-Based Multifunctional Underwater Microrobots -- Medical Applications -- Elastomer Transducers -- Dielectric Elastomer Sensors: Development of Stretchable Strain Sensor System -- Tissue Engineering Approach to Making Soft Actuators -- Integration of Soft Actuators based on a Biomolecular Motor System to Develop Artificial Machines -- Employing Cytoskeletal Treadmilling in Bio-Actuators.
Keywords: Polymers; Biomaterials; Control engineering; Robotics; Automation; Electronics; Polymers; Biomaterials; Control, Robotics, Automation; Electronics and Microelectronics, Instrumentation